Facile Synthesis of N-Phenyl Benzamidine Derivatives, Their Skin Protecting, and Anti-Aging Activity - Taj, M.B.; Tirmizi, Syed Ahmed; Raheel, Ahmad; Alelwani, W.; Hajjar, D.; Makki, Arwa A.; Ali, U.; Darroudi, Majid; Ali, Hapipah Mohd (Pleiades Publishing, 2018)
The straight forwarded new green approach to the synthesis of N-phenyl benzamidine derivatives catalyzed by copper oxide nanoparticles (CuO np ) under solvent-free conditions (without microwave radiations and with MW radiation) is presented. All synthesized compounds 3a–3k are characterized by FT-IR, NMR, and single crystal XRD analysis and tested for their antioxidant and elastase inhibition activities. The compounds 3i and 3j demonstrate significant free radical scavenging activity. The accumulated data indicate that some synthesized compounds can be recognized as good anti-aging agents.